ESPEN endorsed recommendations. Definition and classification of intestinal failure in adults. Issue 2 (April 2015) - Pironi, Loris; Arends, Jann; Baxter, Janet; Bozzetti, Federico; Peláez, Rosa Burgos; Cuerda, Cristina; Forbes, Alastair; Gabe, Simon; Gillanders, Lyn; Holst, Mette; Jeppesen, Palle Bekker; Joly, Francisca; et al.
Summary Background & aims Intestinal failure (IF) is not included in the list of PubMed Mesh terms, as failure is the term describing a state of non functioning of other organs, and as such is not well recognized. No scientific society has yet devised a formal definition and classification of IF. The European Society for Clinical Nutrition and Metabolism guideline committee endorsed its "home artificial nutrition and chronic IF" and "acute IF" special interest groups to write recommendations on these issues. Methods After a Medline Search, in December 2013, for "intestinal failure" and "review"[Publication Type], the project was developed using the Delphi round methodology. The final consensus was reached on March 2014, after 5 Delphi rounds and two live meetings. Results The recommendations comprise the definition of IF, a functional and a pathophysiological classification for both acute and chronic IF and a clinical classification of chronic IF. IF was defined as "the reduction of gut function below the minimum necessary for the absorption of macronutrients and/or water and electrolytes, such that intravenous supplementation is required to maintain health and/or growth". Conclusions This formal definition and classification of IF, will facilitate communication and cooperation among professionals in clinical practice, organization and management, and research.